2010
DOI: 10.1002/pd.2490
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Anencephaly

Abstract: This study provides useful information for health professionals caring for patients with a diagnosis of anencephaly. The majority of these infants die prior to delivery but short-term survival is possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 28 publications
6
44
0
5
Order By: Relevance
“…The two most common types of NTDs are anencephaly, characterized by absence of much of the skull and brain, and spina bifida, a herniation of neural tissue through an incompletely formed spine (Botto et al, 1999). Anencephaly is a lethal condition and liveborn infants typically survive less than one day (Jaquier et al, 2006;Obeidi et al, 2010). The severity of spina bifida is more variable.…”
Section: Introductionmentioning
confidence: 99%
“…The two most common types of NTDs are anencephaly, characterized by absence of much of the skull and brain, and spina bifida, a herniation of neural tissue through an incompletely formed spine (Botto et al, 1999). Anencephaly is a lethal condition and liveborn infants typically survive less than one day (Jaquier et al, 2006;Obeidi et al, 2010). The severity of spina bifida is more variable.…”
Section: Introductionmentioning
confidence: 99%
“…The most important reasons behind parents' happiness after the ultrasound scanning are finding out the baby's gender and receiving guarantee about their health (7). Given the public's increasing awareness about the benefits of ultrasound, demands have increased for performing ultrasound scanning by both doctors and patients (8). Moreover, recent developments in the prenatal diagnostic methods, especially prenatal ultrasound, have resulted in a better understanding of specific congenital anomalies; it has thus led to an improvement in the surgical as well as medical methods of treating birth defects (9).…”
Section: Introductionmentioning
confidence: 99%
“…Isabela et al observed 64% of female anencephalic foetuses in their study (y) The female preponderance also reported by Jaquier et al 12 and James et al, 13 but study by Obeidi et al did not observed female preponderance. 14 Anencephaly associated anomalies ranges from 9.4 to 43%. 11,[16][17][18]20 In present study it was higher (78.12%) than previous studies but similar to study by C. Panduranga et al 73%.…”
Section: Methodsmentioning
confidence: 99%